2009
DOI: 10.2984/049.063.0410
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to the Biocomplexity of Sanak Island, Western Gulf of Alaska

Abstract: The Sanak Biocomplexity Project is a transdisciplinary research effort focused on a small island archipelago 50 km south of the Alaska Peninsula in the western Gulf of Alaska. This team of archaeologists, terrestrial ecologists, social anthropologists, intertidal ecologists, geologists, oceanographers, paleoecologists, and modelers is seeking to understanding the role of the ancient, historic, and modern Aleut in the structure and functioning of local and regional ecosystems. Using techniques ranging from syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 106 publications
(93 reference statements)
1
29
0
Order By: Relevance
“…The archaeological record of the Aleut use of marine species such as the Steller sea lion spans 10 000 years (Laughlin 1980), but well-preserved quantifiable samples are only found from the last 4600 years (Tews 2005;Maschner et al 2008Maschner et al , 2009aBetts et al 2011). Yesner (1980Yesner ( , 1981 points out that the Aleutian region is one of the most productive and biologically diverse ecosystems in the northern hemisphere and that the peoples of the area were poised and equipped to harvest those resources (cf.…”
Section: Population Trends: Long Termmentioning
confidence: 99%
See 1 more Smart Citation
“…The archaeological record of the Aleut use of marine species such as the Steller sea lion spans 10 000 years (Laughlin 1980), but well-preserved quantifiable samples are only found from the last 4600 years (Tews 2005;Maschner et al 2008Maschner et al , 2009aBetts et al 2011). Yesner (1980Yesner ( , 1981 points out that the Aleutian region is one of the most productive and biologically diverse ecosystems in the northern hemisphere and that the peoples of the area were poised and equipped to harvest those resources (cf.…”
Section: Population Trends: Long Termmentioning
confidence: 99%
“…Our field and literature research on western Gulf of Alaska communities found that a mere 1.0% of Sand Point households and 1.3% of King Cove (Maschner et al 2009a), based on house floors, village area and radiocarbon distributions. Our field and literature research on western Gulf of Alaska communities found that a mere 1.0% of Sand Point households and 1.3% of King Cove (Maschner et al 2009a), based on house floors, village area and radiocarbon distributions.…”
Section: Anthropogenic Effects: Fisheries Competition Human Predationmentioning
confidence: 99%
“…First, what have been the roles of prehistoric, historic, and modern Aleut in the structure and functioning of the north Pacific ecosystem and is it possible for that role to continue to viably sustain the communities that live in this ecosystem today? Second, how have major changes in the environment (such as sea level, climate, tsunami, and volcanic eruptions), and social, political, and economic changes (such as migration, colonization, and European expansion), conditioned human social behavior in the context of humanity's role as a key element in the ecosystem engineering and social history of the North Pacific ecosystem [26]. This project was specifically focused to avoid the broad and sweeping generalizations of research such as Jackson et al [69] that sees local people simply as impacts.…”
Section: Methodsmentioning
confidence: 99%
“…They fished for salmon in small streams around the island, and split and salted salmon, storing them in barrels. These were small family operations, but their fishing practices had short-term negative effects on the local salmon runs [26]. These families eventually had to relocate to their present villages on the Peninsula to engage in better fishing and be near the salmon canneries.…”
Section: Cod and Salmon Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation